2017
DOI: 10.1038/srep45867
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone activity during early weaning reprograms molecular markers in rat gastric secretory cells

Abstract: Gastric epithelial cells differentiate throughout the third postnatal week in rats, and become completely functional by weaning time. When suckling is interrupted by early weaning (EW), cell proliferation and differentiation change in the gastric mucosa, and regulatory mechanisms might involve corticosterone activity. Here we used EW and RU486 (glucocorticoid receptor antagonist) to investigate the roles of corticosterone on differentiation of mucous neck (MNC) and zymogenic cells (ZC) in rats, and to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 60 publications
0
31
0
5
Order By: Relevance
“…*P ≤ 0.01, **P ≤ 0.001, ***P ≤ 0.0001. curvature 2 months after adrenalectomy (Supplemental Figure 3B). Glucocorticoids have been reported to stimulate differentiation of parietal and chief cells in neonatal mice (28,29). Adrenalectomy did not reduce the number of parietal cells within the greater curvature but did elicit a 43% decrease in mature chief cells (Supplemental Figure 3, C and D).…”
Section: Adrenal Hormones Are Required To Suppress Spem Developmentmentioning
confidence: 87%
“…*P ≤ 0.01, **P ≤ 0.001, ***P ≤ 0.0001. curvature 2 months after adrenalectomy (Supplemental Figure 3B). Glucocorticoids have been reported to stimulate differentiation of parietal and chief cells in neonatal mice (28,29). Adrenalectomy did not reduce the number of parietal cells within the greater curvature but did elicit a 43% decrease in mature chief cells (Supplemental Figure 3, C and D).…”
Section: Adrenal Hormones Are Required To Suppress Spem Developmentmentioning
confidence: 87%
“…In ZC, the moesin gene encodes a cytoskeleton linker protein that is segregated to the apical membrane of gastric cells where it helps to maintain cell polarity 41 , and Bhlha15 encodes Mist1 transcriptional factor that is involved in organization of pepsinogen granules for secretion 39 . Previously, we showed that in rats, early weaning accelerates the differentiation of MNC 24 and ZC 35 . Of note, we demonstrated that corticosterone is an important element in the machinery that coordinates cellular morphological maturation, and we suggested that the changes are maintained to adulthood, indicating a reprogram of growth 35 .…”
Section: Introductionmentioning
confidence: 93%
“…GR was first described by Munck and Brinck- Johnsen 32 and it is a cytosolic receptor that once activated, rapidly enters the nucleus (t 1/2 = 5–10 min) 33 to bind specific sequences in target genes, which are known as glucocorticoid responsive elements (GRE) 31 , 34 . In the gastric mucosa, GR are expressed during postnatal development and are responsive to circulating glucocorticoids 25 , 35 . In mice and rats, the morphological and functional maturation of gastric mucosa occur concomitant with postnatal development and the glands reach a final configuration by the end of the third week 24 , 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nosso grupo já demonstrou que o DP altera a atividade da corticosterona na mucosa gástrica, elevando os níveis hormonais nos primeiros dias de dieta sólida (Ghizoni et al, 2014), além de provocar uma perda de massa corpórea em filhotes (Gama e Alvares, 2000;Zulian et al, 2017). Outros estudos demonstraram o aumento de populações de CMC e CZ, e de células endócrinas secretoras de ghrelina em filhotes (Osaki et al, 2010;Bittar et al, 2016); Zulian et al 2017), além de alterações da proliferação celular e a espessura da glândula gástrica (Gama e Alves, 2000;Zonta, 2017). Essas modificações ocorrem por meio mecanismos de regulação que envolvem a via de sinalização por MAPK (Alvares e Gama, 1993;Osaki et al, 2011;Osaki e Gama, 2013) e receptores de glicocorticóides (Ghizoni et al, 2014).…”
Section: Amamentação E O Desmame Precoceunclassified